Pathogenic Leptospira Evolved a Unique Gene Family Comprised of Ricin B-Like Lectin Domain-Containing Cytotoxins - Chaurasia, Reetika; Marroquin, Alan S.; Vinetz, Joseph M.; Matthias, Michael A. (Frontiers in Microbiology, 2022)
Leptospirosis is a globally important neglected zoonotic disease. Previous data suggest that a family of Virulence Modifying (VM) proteins (PF07598) is a distinctive feature of group I pathogenic Leptospira that evolved as important virulence determinants. Here, we show that one such VM protein, LA3490 (also known as Q8F0K3), is expressed by Leptospira interrogans serovar Lai, as a secreted genotoxin that is potently cytotoxic to human cells. Structural homology searches using Phyre2 suggested that VM proteins are novel R-type lectins containing tandem N-terminal ricin B chain-like -trefoil domains. Recombinant LA3490 (rLA3490) and an N-terminal fragment, t3490, containing only the predicted ricin B-domain, bound to the terminal-galactosyl-containing glycoprotein, asialofetuin, and directly competed for asialofetuin binding sites with recombinant ricin B chain. t3490 alone was sufficient for binding, both to immobilized asialofetuin and to the HeLa cell surface but was neither internalized nor cytotoxic. Treatment of HeLa cells with rLA3490 led to cytoskeleton disassembly, caspase-3 activation, and nuclear fragmentation, and was rapidly cytolethal. rLA3490 had DNase activity on mammalian and bacterial plasmid DNA. The combination of cell surface binding, internalization, nuclear translocation, and DNase functions indicate that LA3490 and other VM proteins evolved as novel forms of the bacterial AB domain-containing toxin paradigm.